Minimization of Catalyst Loading on Regenerative Fuel Cell Positive Electrodes Based on Titanium Felts using Atomic Layer Deposition. Issue 24 (23rd October 2018) - Schlicht, Stefanie; Barr, Maïssa K. S.; Wu, Mingjian; Hoppe, Paula; Spiecker, Erdmann; Peukert, Wolfgang; Bachmann, Julien
Abstract: We present the preparation and electrochemical analysis of a novel type of positive regenerative fuel cell electrode based on commercially available Ti felts with a Pt/Ir catalyst. Anodic oxidation of the Ti felts leads to the formation of a TiO2 nanotube layer. The high specific surface area allows for a particularly efficient utilization of the noble metal catalyst. Its loading in the nanoporous system is controlled accurately and minimized systematically by atomic layer deposition. The electrochemical activity towards water splitting of both metals is investigated in acidic media by cyclic voltammetry and steady‐state electrolysis for various catalyst loadings. An optimal oxygen evolution reaction is found for a catalyst loading of 76 μg cm −2 resulting in a mass activity of 345 A g −1 at η =0.47 V, whereas the simultaneous presence of Pt at the surface is demonstrated by X‐ray photoelectron spectroscopy and by the high activity observed for the hydrogen evolution reaction. Abstract : Water oxidation reaction is performed on regenerative fuel cell positive electrodes prepared from nanostructured titanium felts coated with platinum and iridium by atomic layer deposition. The method allows for a systematic control of the noble metal catalyst coating and its composition. With this method, the loading can be minimized by a factor 25 with respect to the state of the art.